Pharmacokinetics and bioavailability of ipatasertib in dog plasma using LC/MS/MS. (9th July 2020) - Liu, Ying; Ma, Chunzheng; Jiao, Weijie; Yang, Yanhua; Zhang, Huifang; Du, Lei; Ma, Ming; Sun, Pin; Li, Xiaokun; Chen, Jianshe
Abstract: A rapid, sensitive, and reliable liquid chromatography‐tandem mass spectrometric method was developed to quantify ipatasertib in dog plasma. The dog plasma sample was deproteinated by using acetonitrile with ulixertinib as an internal standard followed by separation on a Spursil C18 ‐EP column with a gradient mobile phase comprising 2 mM ammonium acetate containing 0.1% formic acid and acetonitrile. Positive ion electrospray was used, and multiple reaction monitoring transitions were m/z 458.2 > 387.2 for ipatasertib and m/z 433.1 > 262.1 for the internal standard. The developed method was validated with a linear range of 0.3–1500 ng/mL, and with correlation coefficient greater than 0.9989. The lower limit of quantification was 0.3 ng/mL. The intra‐ and inter‐day precision ranged from 3.58 to 14.32%, whereas the intra‐ and inter‐day accuracy was in the range of −2.50–13.25%. No carry‐over and matrix effects were observed under the current conditions. The extraction recovery was demonstrated to be greater than 85.43%. Ipatasertib was stable during the storage, processing, and determination. The validated assay was further successfully applied to a pharmacokinetic study of ipatasertib in dogs after oral and intravenous administrations. The bioavailability of ipatasertib was determined to be 19.3%.